THE EFFECT OF ROSELLA DRIED CALYX INFUSION (HIBISCUS SABDARIFFA) IN LOWERING LDL CHOLESTEROL SERUM LEVEL ON CIGARETTE SMOKE EXPOSED MALE SPRAGUE DAWLEY RATS - Gabriela Rolanda; Lusiana Batubara; Indah Saraswati; Kusmiyati Tjahjono DK (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Background: Cigarettes increase cardiovascular risks by modifying lipid profiles through oxidation, alternating lipoprotein composition, and fat metabolizing enzyme activity. Vascular dysfunction can primarily identified by LDL cholesterol composition shift, one of atherosclerosis predictor. Rosella is a multifunctional herb that widely used as a pleasant tea. Aside from its rich components, anthocyanin, pectin, PCA and hibiscus acid are playing the role keys in lowering LDL cholesterol through lipid metabolism enzyme activity modification. Rosella is easy to find, relatively cheap, tasteful and also categorized as food-grade FDA approved.Aim: To investigate the effect of rosella infusion in decreasing LDL cholesterol serum on cigarettes exposed male Sprague dawley rat.Methods: This study is a true experimental study design with post-test only controlled group design. After 7 days of adaptation, a total of 30 male Sprague dawley rats were randomly divided into 5 groups (n=6 per group); KN received no special treatment; KP exposed to 4 rods of cigarette smoke/day; experimental groups (P1, P2, P3) exposed to 4 rods of cigarette smoke/day and rosella dried calyx infusion with 250, 500 and 1000 mg/kg respectively for 30 consecutive days. LDL cholesterol levels are measured using the CHOD-PAP method. Collected data were analyzed statistically using One Way ANOVA Test.Results: There is a significant difference between all experimental groups (p=0,00) in the post-hoc test.Conclusion: These lines of evidence suggest that rosella infusion significantly decreases LDL Cholesterol serum level in cigarettes exposed Sprague dawley rats in a dose-dependent manner.Keywords: Cigarettes smoke, LDL cholesterol, Rosella calyx infusion